Drying of Anchovies (Stolephorus indicus) in a Solar Polythene Tent - Punna Reddy, K.; Sudhakara, N.S.; Rudra Setty, T.M.; Surya Prakash Rao, V. (Fishery Technology, 2025)
The drying parameters of anchovies dried in solar tent dryer and under sun are compared. Though the temperature inside the tent was 14-15Â°C higher than the ambient temperature during early aftemoonin sunny days the drying rate did not show any significant difference between the two methods. Hence solar tent dryer offered little merit but for the protection given by tent against dust, insects, birds or sudden shower.